HUBUNGAN JUMLAH TROMBOSIT DAN NILAI HEMATOKRIT TERHADAP DERAJAT KEPARAHAN DEMAM BERDARAH DENGUE - Desima Tamara Sinurat; Thomas Silangit; Alexander P. Marpaung (Majalah Ilmiah METHODA, 2020)
Dengue infection is a public health problem in Indonesia in general and North Sumatra in particular, where the cases tend to increase and spread more widely and have the potential to cause outbreaks. Platelets and hematocrit are important parameters in the management of patients with dengue infection. To determine the relationship between platelets counts and hematocrit with the severity of dengue infection, a literature review was conducted by comparing several related journals. The research method used was a Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were five journals with inclusion criteria for the publicaton date of the last five years, the language used was Indonesian, with the research subjects of patients with a diagnosis of dengue hemorrhagic fever and full text publication. There is a significant relationship between the plateled count and the hemtocrit value with the severity of the dengue infection patients, but there is dengue hemorrhagic fever patients.